Analisis Akuntabilitas Partai Politik dan Bantuan Keuangan dalam Konteks Demokrasi Indonesia - Yamin, Muhammad; Rosyadi, Slamet; Runtiko, Agus Ganjar; Kurniasih, Denok; Wijaya, Shadu Satwika; Darmawan, Arif; Satyawan, Darmanto Sahat; Wahyuningrat; Isna, Alizar; Sulaiman, Adhi Iman; Novianti, Wiwik (Ministry of Home Affairs, 2024)
In the contemporary era characterized by globalization and swift democratic progress, Indonesia encounters distinctive challenges of rising political expenses. This article utilizes qualitative research methodologies to examine the consequences of increasing political costs on the dynamics of Indonesian democracy, specifically concerning accountability and financial support for political parties. The main findings suggest that the financial assistance to political parties in Indonesia has not adequately tackled the forthcoming challenges that Indonesian democracy may encounter. In contrast, political parties persist in facing challenges in accountability mechanisms for the funds they acquire. The provision of financial aid may be perceived as a feasible approach to mitigate the financial burdens associated with political campaigns. However, in the absence of adequate mechanisms to ensure transparency and accountability, there is a possibility of corruption and concerns regarding the scope of funding. This article further emphasizes the significance of political education as a fundamental obligation of political parties to uphold democratic efficacy. This study places particular emphasis on the ramifications of providing financial assistance to political parties for the future trajectory of Indonesian democracy. To ensure the continued progress of democracy in Indonesia and realize the “Golden Indonesia 2045” vision, stakeholders must possess a comprehensive comprehension of the matter and effectively tackle the obstacles that arise from the significant political expenses involved.